1998
DOI: 10.1243/0954405981515509
|View full text |Cite
|
Sign up to set email alerts
|

Influence of exit angle and tool nose geometry on burr formation in face milling operations

Abstract: One of the more important burrs produced in a face milling operation is the burr formed on the exit edge in the cutting direction. This burr is present over the full length of the exit edge, and under certain cutting conditions is relatively large in size, strongly attached to the workpiece, and presents a strong configuration, features that make it difficult to remove and consequently increases the cost of the component. This paper is concerned with the influence of the exit angle and tool nose geometry on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 10 publications
0
27
0
Order By: Relevance
“…The primary burr protruded from the machined part and became more pronounced; hence their lengths were controlled throughout the tests. Olvera and Barrow [11] reported an increase in burr length with increasing exit angles (from 308 to 1508). In this study the maximum burr length was found at an exit angle, m , of 908.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…The primary burr protruded from the machined part and became more pronounced; hence their lengths were controlled throughout the tests. Olvera and Barrow [11] reported an increase in burr length with increasing exit angles (from 308 to 1508). In this study the maximum burr length was found at an exit angle, m , of 908.…”
Section: Resultsmentioning
confidence: 95%
“…This process is highly a ected by the depth of cut, exit angle of the milling cutter and tool geometry. Increase in the depth of cut beyond 0.4 mm reduces the loss of material at the secondary burr, consequently reducing the size of the primary burr [11]. The objective of this work is to study the formation of burr at the exit region of the workpiece, the surface quality and their relation to tool wear.…”
Section: Introductionmentioning
confidence: 99%
“…In their study, increasing radial rake angles lead to a reduction in burr formation. A considerable influence of the axial rake angle on burr formation was not found (Olvera and Barrow, 1998). In comparison to up milling, down milling is to prefer concerning burr reduction (Olvera and Barrow, 1996).…”
Section: Analysis Of Existing Researchmentioning
confidence: 88%
“…Longer burrs in the cutting direction are formed when larger corner radii are used. Olvera and Barrow [40] found that the exit angle and the depth of cut influence the exit burr in the cutting direction, whereas the depth of cut is the main factor affecting the exit burr in the feed direction. According to [41,42], the use of high levels of axial depth of cut increases the possibility of burr size minimization, but may also cause inevitable damage to the cutting tool, the machine and machined part functionality.…”
Section: Cutting Conditionsmentioning
confidence: 99%